Analisis Pembiayaan Murabahah Bermasalah (Studi Kasus pada BMT Nurul Ummah) - Syukia Rahma, Fujianti Lestari (COMPETITIVE, 2023)
Analysis of Problematic Murabahah Financing (Case Study on BMT Nurul Ummah). Thesis, Accounting Study Program, Faculty of Economics, University of Muhammadiyah Sukabumi 2021.Murabahah is one of the finanving that is in great demand by many people, from some financing that is in a sharia financial institution, murabahah must have a fairly large number of customers. However, many customers do not guarantee the smoothness that occurs in the financing. In the last 2 years, BMT Nurul Ummah has experienced a decline quality of murabahah financing. There are several factors that make murabahah problematic, one of which in a weak analysisi, in addition to goverment policies during the Covid-19 pandemic. In addition to factors, there is also a solution, one of which is by implementing restructuring.Keywords: Murabahah, Problematic Financing rescue, Restructuring..